THE ROLE OF CAPITAL STRUCTURE IN MODERATING LIQUIDITY, PROFITABILITY AND FIRM SIZE - Berta Shania Ayu Wulandari; Hans Hananto Andreas (KRISNA: Kumpulan Riset Akuntansi, 2025)
This study aims to determine the effect of liquidity, profitability, and company size on firm value by using capital structure as a moderating variable. This study uses a quantitative method with a research sample of manufacturing companies listed on the Indonesia Stock Exchange (IDX) using 143 company samples in the 2021-2023 period. The research methods used are panel data regression, multiple regression analysis, and moderation regression analysis. This study proves that liquidity and company size have a negative effect, while profitability has a positive effect on firm value. Capital structure does not moderate the relationship between liquidity and firm size on firm value. However, capital structure is stated to be able to weaken the relationship of profitability to firm value. Keyword: Liquidity, Profitability, Firm Size, Firm Value, Capital Structure